TIKTOK SHOP VS E-COMMERCE VS NEGARA: MENCARI TITIK KESEIMBANGAN DALAM BINGKAI EKONOMI KONSTITUSIONAL - Anuar, Yazrul; Hazmi, Raju Moh; Nazar, Jasman (Law Jurnal, 2023)
This article aims to understand the concept of e-commerce and find a balance point in the constitutional economic framework regarding the prohibition on social media, TikTok shops merging into e-commerce. This research uses a juridical-nornative approach and is designed to be descriptive. The research results show: The concept of e-commerce is basically a "container" for business people who sell and makes it easier for them to connect with consumers online and carry out their activities practically and efficiently. Transactional procession activities through the world of e-commerce involve two parties, namely business actors and consumers. Tiktok shop since this writing has not met the criteria for e-commerce as mandated by PP Number 80 of 2019. On this side, constitutional economic balance is needed to bridge interaction and connectivity between society, the state and the market. This means that the government must ensure healthy business competition and protection for society as a whole for the products offered specifically in e-commerce activities. considering that production from upstream to downstream is a long economic process. This is in line with the will of the Indonesian state as stated in the economic conception of the constitution in Article 33 of the 1945 Constitution of the Republic of Indonesia which is based on the principles of balance, justice and sustainability.